The Effect of Cement Stabilized Subgrade on Cost of the Flexible Pavement - Kok, Baha Vural; Yilmaz, Mehmet; Geckil, Alaaddin (Pamukkale Univ, 2012)
The road authorities aim roads that are resistant, with less maintenance, with high traffic security, with long life and economic. It is difficult to have an economic pavement construction on the subgrade with weak bearing capacity. In this study the effect of the cement stabilization on the weak subgrade and pavement costs has been studied. For this purpose the California Bearing Ratio (CBR) of a weak subgrade that has been stabilized with 4% - 16% cement have been determined. The effect of the increase in the CBR on the pavement costs has been determined thanks to MATLAB program by considering thousands of alternatives. Consequently, the optimum cement content between the decrease on the pavement costs with increase on subgrade' CBR value and the additional costs spent to increase the CBR value has been determined.
Keywords: Cement; Stabilisation; Flexible pavement; Cost